Correlation of foot posture Index-6 and navicular drop test with functional ankle stability in running athletes in New Delhi - Jyoti Kataria; Manish Kumar; Supriya Awasthi (Al Ameen Medical College, 2020)
Introduction: Human foot posture is highly variable among healthy individuals and ranges from flat- to high-arched. Considering the hypothesized link between foot posture and lower extremity injury, static foot posture is frequently assessed in the clinical setting, with a belief that this may provide indications for biomechanical interventions (e.g. foot orthoses). The Foot Posture Index (FPI) is a validated method for quantifying standing foot posture. Navicular drop test is used in evaluating the amount of pronation in runner's foot. However, studies need to be done to identify if the tools used to measure Foot posture and stability can be correlated and used to predict the outcome of other with the help of one score. Aims & objective: To identify the correlation of FPI-6 and NDT with Functional Ankle Stability in Running Male Athletes. Method: 60 running athletes were included in the study. FPI-6 and NDT were calculated for each athlete to measure the foot posture along with Side-hop test to analyze the functional ankle stability. Results: FPI- 6, NDT, Functional Ankle Stability using side hop test were calculated of both the feet. We found there is significant correlation between the FPI- 6, NDT and Side Hop Test. Conclusion: Results show that there is significant correlation between Navicular Drop Test with Functional Ankle Stability in Running Male Athletes. And there is significant correlation between Foot Posture Index-6 and Functional Ankle Stability in Running Male Athletes.